LOYALITAS MASYARAKAT KAMPUNG ADAT CIREUNDEU DALAM MEMPERTAHANKAN BAHASA IBU - Tati Purwasih; Regina Ariesta Filia; Teti Sobari (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research is motivated by the number of mother languages that experience shifts and are even threatened with extinction, if language maintenance is not carried out. This study aims to determine the loyalty of the people of Cireundeu traditional village in maintaining their mother tongue. The use of descriptive qualitative methods is applied to the data obtained in the form of local wisdom Cireundeu traditional village as a tourist location. The consistency of the Cireundeu indigenous people in safeguarding and preserving the local wisdom participated in maintaining their mother tongue, namely Sundanese. This can be proven from the results of research, namely (1) the use of Sundanese as a means of social communication, (2) Sundanese as the language of instruction in religious ceremonies, (3) expressions of Cireundeu indigenous people's beliefs. Furthermore, this research is expected to be able to build positive language awareness and enrich sociolinguistic studies, especially regarding language maintenance.